The relationship between prenatal drought exposure and the diversity and composition of gut microbiome in pregnant women and neonates - Qingbo Fang; Tianlai Qiu; Fenglan Chen; Xuqi Tian; Zijun Feng; Yanan Cao; Jinbing Bai; Jing Huang; Yanqun Liu (Scientific Reports)
Abstract Drought induced by climate change poses a serious threat to human health. The gut microbiome also plays a critical role in human health. However, no studies have explored the effect of drought on the human gut microbiome. Therefore, our study aimed to investigate the relationship between drought and gut microbiome. Our study included 59 mothers and 38 neonates in our study. 16S rRNA V3-V4 sequencing was used to profile the gut microbiome. The Standardized Precipitation Evapotranspiration Index (SPEI) was used to represent drought characteristics. KEGG pathway level 3 was employed for functional analysis. Generalized linear models were used to explore the effect of drought on the gut microbiome. Mothers and neonates were divided into the LSPEI (Lower SPEI) group or HSPEI (Higher SPEI) group by calculating the average levels of prenatal SPEI levels. The maternal and neonatal gut microbiome exhibited similar diversities in terms of alpha and beta diversity between the LSPEI and HSPEI groups. However, notable differences were observed in their composition. We found that in the neonatal gut microbiome, Sediminibacterium and Thermovirga were positively associated with SPEI after controlling for PM2.5 in linear regression models. Additionally, SPEI was significantly associated with phenylpropanoid biosynthesis and cyanoamino acid metabolism in neonates. This study identified that prenatal SPEI levels were correlated with specific maternal and neonatal gut microbial taxa, as well as neonatal gut microbial functional pathways. Future studies should further investigate the mechanisms by which drought exposure influences maternal and neonatal gut microbial diversities, composition, and functional pathways.